2001
DOI: 10.1007/s004240100677
|View full text |Cite
|
Sign up to set email alerts
|

Confocal microscopy study of the different patterns of 2-NBDG uptake in rabbit enterocytes in the apical and basal zone

Abstract: D-Glucose uptake in isolated rabbit enterocytes was studied using confocal microscopy and 2-[N-(7-nitrobenz-2-oxa-1,3-diazol-4-yl)amino]-2-deoxy-D-glucose (2-NDBG), a D-glucose fluorescent analogue, by analysing the fluorescence of apical and basal enterocyte zones. Under normal conditions, apical fluorescence was always higher than basal, presumably due to the location of the Na+-D-glucose cotransporter in the brush-border membrane. After blocking this transporter with phlorizin, apical and basal fluorescence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 22 publications
3
11
0
Order By: Relevance
“…The fluorescent dye 2-NBDG was a good tool to study glucose transport. We found that the dye is incorporated into freshly isolated rabbit enterocytes through glucose transporters as it was previously demonstrated in other cellular models (5)(6)(7)(9)(10)(11). The 2-NBDG was actively transported and accumulated in cells to a steady-state level that depended upon its extracellular concentration, the glucose transport capacity of the cells, and the intracellular degradation Figure 6.…”
Section: Discussionsupporting
confidence: 71%
“…The fluorescent dye 2-NBDG was a good tool to study glucose transport. We found that the dye is incorporated into freshly isolated rabbit enterocytes through glucose transporters as it was previously demonstrated in other cellular models (5)(6)(7)(9)(10)(11). The 2-NBDG was actively transported and accumulated in cells to a steady-state level that depended upon its extracellular concentration, the glucose transport capacity of the cells, and the intracellular degradation Figure 6.…”
Section: Discussionsupporting
confidence: 71%
“…We observed the cellular uptake of 2-NBDG in the proximal tubule was similar from the apical and basolateral side of the cell, suggesting uptake by both SGLT and the glucose transporter (GLUT) as observed in studies in isolated cells (2,7,23,33).…”
Section: D)supporting
confidence: 69%
“…8 Consistently, glucose uptake was higher in HEPTECs from diabetes patients than in controls. Radiolabeled substrate, 14 C-labeled a-methyl-d-glucopyranoside ([ 14 C]AMG), is commonly used to measure SGLTmediated glucose uptake in primary cultures of human or animal PT cells and in the PT cell line LLC-PK 1 . [8][9][10] Similarly, we have used [ 14 C]AMG in our toxicological studies to show the inhibitory effect of cadmium on SGLT activity.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 A fluorescent derivative of glucose, 2-(N-(7-nitrobenz-2-oxa-1,3-diazol-4-yl)amino)-2-deoxyglucose (2-NBDG), is available. 13 Microscopy can be performed to examine 2-NBDG uptake in living cells, 14 and the intracellular concentration of transported 2-NBDG can be measured with fluorescence spectroscopy. 15 In enterocytes, 2-NBDG uptake could be blocked with phlorizin, an inhibitor of SGLTs, 14,16 whereas cytochalasin B, a GLUT inhibitor, cells, 18,19 suggesting that 2-NBDG is transported by SGLTs and GLUTs.…”
Section: Introductionmentioning
confidence: 99%